TRANSFORMASI DIGITAL SISTEM PENJAMINAN MUTU INTERNAL BERBASIS APLIKASI BSC-SM UNTUK MEWUJUDKAN PENDIDIKAN BERKUALITAS PADA MGMP EKONOMI JAWA TENGAH - Ahmad Sehabuddin; Indri Murniawaty; M. Faris Al-Hakim; Lusiana Ira Agustian; Nur Intan Sapitri; Risma Aprilia; Cindy Eka Putri (Jurnal Abdi Insani, 2026)
The Economics Subject Teachers’ Forum (MGMP) of Central Java plays a strategic role in improving the quality of education at the senior high school level. However, the implementation of the Internal Quality Assurance System in the participating schools still faces various challenges, particularly due to the lack of integration with digital technology, which has resulted in ineffective and inefficient practices. This condition has led to low accuracy in quality mapping, delays in strategic planning, and a strong reliance on manual processes. This community service activity aims to enhance the capacity of Economics MGMP teachers in Central Java to implement a digital-based IQAS through the utilization of the Balanced Scorecard-School Management (BSC-SM) application. The activity employed several methods, including socialization, training, technology implementation, mentoring, and periodic evaluation involving 40 Economics MGMP teachers in Central Java. The results demonstrate a significant improvement in participants’ ability to use the BSC-SM application, analyze IQAS outcomes, and develop data-driven short-term and long-term strategic plans. This improvement is evidenced by the average total achievement rate, which increased from 39.04% before the training to 94.28% after the training. The implementation of the BSC-SM application has proven effective in enhancing the effectiveness, efficiency, and accuracy of IQAS implementation in schools. Therefore, this community service activity contributes to supporting the digital transformation of educational quality assurance and the realization of quality education within the Economics MGMP of Central Java.